Viola pachysoma (Violaceae), a new name for a rosulate species endemic to the Andes of Argentinian Patagonia - Watson, John M.; Flores, Ana R.; Sheader, Martin; Sheader, Anna-Liisa (Phytotaxa, 2018)
The species herein, Viola pachysoma, has a long history of confused identity. When recognised as a distinct taxonomic entity it was published as Viola copahuensis. It also acquired a later replacement name, Viola caviahuensis. Each of these in turn has been formally declared nom. illeg. et nom superfl. Consequently, a third epithet for the taxon, V. pachysoma, is coined and presented here. The original protologue lacked a formal diagnosis, so we have added a supplementary version. We also chronicle the species since known to science, including its status as one of the parents of the first recorded hybrid in its section. A discussion and two multi-character tables serve to compare and separate species comprising the poorly understood geographical alliance which incorporates V. pachysoma.